Management of Epirubicin Extravasation Injuries of the Hand with Debridement and Flap Cover—A Case Series - Yellinedi, Rajesh; Damalachervu, Mukunda Reddy; Nuvvula, Rambabu; Thammineedi, Subramanyeshwar Rao (Indian Journal of Plastic Surgery, 2023)
Chemotherapy extravasation injury is an iatrogenic injury due to extravasation of the drug from the vessel during infusion therapy. Among various chemotherapeutic drugs, DNA binding vesicants like epirubicin and doxorubicin can lead to extensive tissue necrosis following extravasation. They are commonly used in many chemotherapy regimens including those for carcinoma breast. We present our case series in the management of these wounds with aggressive debridement and regional (pedicled groin)/free flaps (superficial circumflex iliac artery perforator, lateral arm) for cover in five patients. All flaps healed well with patient returning to further treatment in 3 to 4 weeks post-surgery with preservation of hand function. Thus, early recognition of the type of drug that has extravasated is crucial. Regional and free flaps are superior to local flaps because there are no extra incisions and grafts on the limb that has already been injured.
Keywords: chemotherapy extravasation; vesicants; free flap cover